The Role of Dissolved Oxygen in Hard Clam Aquaculture - Kerry Weber; Elise Hoover; Leslie Sturmer; Shirley Baker (EDIS)
FA152, an 11-page illustrated fact sheet by Kerry Weber, Elise Hoover, Leslie Sturmer, and Shirley Baker, discusses dissolved oxygen in clam leases, how to monitor varying concentrations, signs of oxygen stress, how it affects hard clam production, and how to develop a management strategy to adapt to dissolved oxygen levels. Includes contact information for state specialists, glossary and further readings. Published by the UF Program of Fisheries and Aquatic Sciences of the School of Forest Resources and Conservation, December 2008.